Studi Essensial Marketing Pada Ritual Adat “Nyadhar” Madura - Nur Latifa Isnaini Putri (Journal of Management and Social Sciences, 2023)
Value that exists in a cultural customary ritual entity in a community environment, will not become a potential if its essence has not been determined. Essential marketing strategy is a marketing strategy that focuses on the core or basis of marketing. This study aims to find a marketing strategy to develop Sumenep based on culture that has been upheld by the people so far. This research is a qualitative research and uses a purposive method in selecting informants. Informants in this study were Pinggirpapas village community leaders, Pinggirpapas village community, and Pini Sepuh as traditional ritual leaders. The results of this study are a form of marketing essential values in Nyadar traditional rituals including; The Sanctity of Traditional Ritual Processions, Transformation of customary values between generations that bind as resilience to the psychological aspects of the residents, and the residents belief in the uniqueness of the ritual. While the economic strategy built by the residents is the inherent religious, cultural and economic values as well as the empowerment of economic values for processional products and a variety of local traditional and village culinary offerings. Furthermore, this research can become the basis for the government in developing the concept of city branding in Sumenep as an effort to increase the number of tourists visiting.